«О личности и о факультете международных отношений» – посвящается первому декану ФМО Гульжаухар Шагатаевне Жамбатыровой - Губайдуллина, М. Ш. (International relations and international law Journal, 2016)
"About the personality and about the faculty of the international relations" – it is devoted to the first dean of FIR - Zhambatyrova Gulzhauhar Shagatayevna «Жеке тұлға туралы және халықаралық қатынастар факультеті туралы» – ХҚФ-нің алғашқы деканына, Гүльжауһар Шағатайқызы Жамбатыроваға, арналады